2022
DOI: 10.1149/1945-7111/ac5345
|View full text |Cite
|
Sign up to set email alerts
|

Operando Synchrotron Studies of Inhomogeneity during Anode-Free Plating of Li Metal in Pouch Cell Batteries

Abstract: Operando synchrotron X-ray diffraction (XRD) studies have not previously been used to directly study Li metal in standard batteries due to the extremely weak scattering from Li atoms. In this work, it is demonstrated the stripping and plating of Li metal can be effectively quantified during battery cycling in appropriately designed synchrotron XRD experiments that utilize an anode-free battery configuration in which a Li-containing cathode material of LiNi0.6Mn0.2Co0.2O2 (NMC622) is paired with a bare anode cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In anode-free pouch cells with NCM622 cathode and Cu or Mo anode current collector, the local variation of electrode materials was tracked through the operando synchrotron X-ray diffraction. [81] It was found that the initial Li deposition is quite uniform, while pronounced inhomogeneity at an mm-scale was observed during the subsequent Li stripping process. In addition, the rates of Li utilization have a strong spatial correlation between the cathode and anode.…”
Section: Homogeneity Of Electrode Materialsmentioning
confidence: 96%
“…In anode-free pouch cells with NCM622 cathode and Cu or Mo anode current collector, the local variation of electrode materials was tracked through the operando synchrotron X-ray diffraction. [81] It was found that the initial Li deposition is quite uniform, while pronounced inhomogeneity at an mm-scale was observed during the subsequent Li stripping process. In addition, the rates of Li utilization have a strong spatial correlation between the cathode and anode.…”
Section: Homogeneity Of Electrode Materialsmentioning
confidence: 96%
“…(see Figure 3) Last but not least, it is also worth to mention that recent operando studies in optimized conditions at 107.7 keV (0.1173Å) have permitted to follow the homogeneity of the lithium plating/stripping process in an "anode-free" pouch cell, despite lithium low scattering factor. 46 Pair Distribution Function analysis (PDF)…”
Section: Elastic Scattering Based Techniquesmentioning
confidence: 99%
“…In addition to EPRI technology, an operando synchrotron study was also performed to analyze the stripping and plating of Li metal in AFLPBs. 84 As shown in Fig. 10b, the local performance diagrams of the anode and cathode in the pouch cell were compared.…”
Section: Promotion Strategies and Failure Analysis Of Aflpbsmentioning
confidence: 99%